PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN DALAM PEMBERIAN KARTU KREDIT DENGAN METODE MFEP (MULTI FACTOR EVALUATION PROCESS ) - Yasni Jamain (Jurnal Teknik, 2015)
The credit card is a necessity for modern society to support all activities in their daily lives . One of them as a means of payment used to pay for e - comerce on the internet . But the problem is so many customers who apply for a credit card so as to select the feasibility of credit card recipient took quite a long time because the process for selecting still manual .The method for selecting candidates for customers with existing criteria using MFEP ( Multi Factor Evaluation Process ) . By using this method the process of selecting the best alternative use " weighting system " . In MFEP all criteria become an important factor in doing consideration given appropriate weighting . Key Word : Credit card, Weighting System